2023
DOI: 10.3390/su15010786
|View full text |Cite
|
Sign up to set email alerts
|

Fishmeal Replacement by Full-Fat and Defatted Hermetia illucens Prepupae Meal in the Diet of Gilthead Seabream (Sparus aurata)

Abstract: Insect proteins are considered as suitable low environmental impact alternatives to fishmeal for sustainable aquafeeds. Among the different insect species, Hermetia illucens has attracted research and industrial interest due to its ability to grow well on organic side streams, its high protein content and favorable amino acid profiles. Its lipid content although high is characterized by a lack of EPA and DHA that are essential to fish nutrition and thus a defatted form of Hermetia meal might be of better use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 84 publications
1
15
1
3
Order By: Relevance
“…According to Karapanagiotidis et al [96], the replacement of FM with HI meal in sea bream juveniles was up to 30%, corresponding to an inclusion level of 27.6%, which did not afect the fsh growth, although FW and WG were signifcantly lower (P < 0.05) in fsh feeding on prepupae meal-based diets.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Karapanagiotidis et al [96], the replacement of FM with HI meal in sea bream juveniles was up to 30%, corresponding to an inclusion level of 27.6%, which did not afect the fsh growth, although FW and WG were signifcantly lower (P < 0.05) in fsh feeding on prepupae meal-based diets.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, to date, only few studies have been performed on the use of HIM as a partial replacement of fsh meal in the sea bream feed [73,74,77], but they are mainly focused on the lipid composition of fllets. Also, Pulido-Rodriguez et al [78] and Randazzo et al [79] reported results on the use of HIM in the diet of gilthead sea bream but as a replacement for vegetal proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published studies using H. illucen s meal for fishmeal replacement have been conducted majorly in farmed fish species such as rainbow trout ( Stadtlander et al, 2017 ), Atlantic salmon ( Li et al, 2020 ), European sea bass ( Magalhães et al, 2017 ), gilthead seabream ( Karapanagiotidis et al, 2023 ), African catfish ( Fawole et al, 2020 ), Nile tilapia ( Tippayadara et al, 2021 ) and yellow catfish ( Xiao et al, 2018 ), and only few in crustaceans such as pacific white shrimp ( Cummins et al, 2017 ) and red claw crayfish ( Wang et al, 2022 ). For P. leptodactylus , Mazlum et al (2021) evaluated the use of Tenebrio molitor and reported that a dietary inclusion level of 13.5%, representing 50% of fishmeal replacement, was successful in terms of growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Τα έντομα μπορούν να αποτελέσουν μια διατροφικά κατάλληλη και παράλληλα αειφόρο εναλλακτική λύση των ιχθυαλεύρων δεδομένου ότι η χρήση τους παρουσιάζει πολλά πλεονεκτήματα. Καταρχάς, τα έντομα, αναλόγως του είδους και του σταδίου ανάπτυξης τους, περιέχουν υψηλά επίπεδα πρωτεϊνών (έως και 70% της θρεπτικής τους σύστασης) και λίπους (έως και 55%), γεγονός που θα μπορούσε να παρέχει κατάλληλες ποσότητες θρεπτικών συστατικών στη διατροφή των ιχθύων(Barroso et al 2014, Karapanagiotidis et al 2015.Παράλληλα, είναι πλούσιες πηγές των απαραίτητων αμινοξέων, πολλών βιταμινών και ανόργανων στοιχείων, ενώ κάποια είδη εντόμων περιέχουν ικανοποιητικά επίπεδα σε ω-3 και ω-6 πολυακόρεστα λιπαρά οξέα(Sánchez-Muros et al 2014). Επίσης, δεν θα πρέπει να αγνοείται το γεγονός πως τα έντομα αποτελούν τη φυσική τροφή πολλών ειδών ιχθύων, τόσο του γλυκού όσο και του θαλασσινού νερού(Henry et al 2015).…”
unclassified
“…Παράλληλα, η εκτροφή των εντόμων πραγματοποιείται σε μικρούς και κλειστούς χώρους, χωρίς την απαίτηση μεγάλων εκτάσεων γης και κατανάλωσης νερού, αλλά με χαμηλής τεχνολογίας μέσα και χαμηλής επένδυσης(Sánchez-Muros et al 2014). Περαιτέρω, λόγω του γεγονότος ότι είναι εξώθερμοι οργανισμοί αποτελούν πολύ αποτελεσματικούς μετατροπείς τροφή, καθώς δεν ξοδεύουν μεταβολική ενέργεια για τη διατήρηση της θερμοκρασίας του σώματος τους(Nijdam et al 2012).Οι διάφορες μελέτες που έχουν πραγματοποιηθεί μέχρι σήμερα με τη χρησιμοποίηση εντομαλεύρων των ειδών Tenebrio molitor και Hermetia illucens στο σιτηρέσιο της τσιπούρας έχουν δείξει ότι είναι εφικτή μια μερική υποκατάσταση του ιχθυαλεύρου της τάξης του 25-30%(Karapanagiotidis et al 2015, Piccolo et al 2017. Εν τούτοις, και παρά το γεγονός πως από το 2017 επιτράπηκε η χρησιμοποίηση των εντομαλεύρων από 7 είδη εντόμων στις ευρωπαϊκές ιχθυοτροφές (ΕΚ 893/2017), ο κλάδος παρασκευής ιχθυοτροφών σήμερα παραμένει διστακτικός ως προς την ενσωμάτωσή τους στα σιτηρέσια.…”
unclassified